Neonatal presentation of genetic epilepsies: Early differentiation from acute provoked seizures. (21st June 2021) - Cornet, Marie‐Coralie; Morabito, Valeria; Lederer, Damien; Glass, Hannah C.; Ferrao Santos, Susana; Numis, Adam L.; Ferriero, Donna M.; Sands, Tristan T.; Cilio, Maria Roberta
Abstract: Objective: Although most seizures in neonates are due to acute brain injury, some represent the first sign of neonatal onset genetic epilepsies. Delay in recognition and lack of expert assessment of neonates with epilepsy may result in worse developmental outcomes. As in older children and adults, seizure semiology in neonates is an essential determinant in diagnosis. We aimed to establish whether seizure type at presentation in neonates can suggest a genetic etiology. Methods: We retrospectively analyzed the clinical and electroencephalographic (EEG) characteristics of seizures in neonates admitted in two Level IV neonatal intensive care units, diagnosed with genetic epilepsy, for whom a video‐EEG recording at presentation was available for review, and compared them on a 1:2 ratio with neonates with seizures due to stroke or hypoxic–ischemic encephalopathy. Results: Twenty neonates with genetic epilepsy were identified and compared to 40 neonates with acute provoked seizures. Genetic epilepsies were associated with pathogenic variants in KCNQ2 ( n = 12), KCNQ3 ( n = 2), SCN2A ( n = 2), KCNT1 ( n = 1), PRRT2 ( n = 1), and BRAT1 ( n = 2). All neonates with genetic epilepsy had seizures with clinical correlates that were either tonic (18/20) or myoclonic (2/20). In contrast, 17 of 40 (42%) neonates with acute provoked seizures had electrographic only seizures, and the majority of the remainder had clonic seizures. Time to first seizure was longer in neonates with genetic epilepsies (median = 60 h of life) compared to neonates with acute provoked seizures (median = 15 h of life, p < .001). Sodium channel‐blocking antiseizure medications were effective in 13 of 14 (92%) neonates with tonic seizures who were trialed at onset or during the course of the epilepsy. Significance: Seizure semiology is an easily accessible sign of genetic epilepsies in neonates. Early identification of the seizure type can prompt appropriate workup and treatment. Tonic seizures are associated with channelopathies and are often controlled by sodium channel‐blocking antiseizure medications.